The Networking Survival Guide, Second Edition - Darling, Diane (Ascent Audio, 2019)
No matter how smart and talented you are, you need the help of others to reach your true potential. Solid connections with the right people are just as important as being good at what you do. This fully revised edition of The Networking Survival Guide reveals tried and true networking tactics, as well as new ways to harness the extraordinary influence of social networking sites like Facebook, LinkedIn, and Twitter. It teaches you how to: - Identify and develop mutually beneficial relationships - Create a strategy so your network is in place before you need it - Succeed at networking even if you're an introvert - Use the proper etiquette in any situation - Turn conversations into opportunities - Become a resource for fellow networkers.
Online resource; Title from title page (viewed April 9, 2019)
Keywords: Self-help; Audiobooks